The Role of Endothelial Progenitor Cells in Coronary Artery Disease: Basic Molecular Mechanisms and Its Clinical Potentials - Yudi Her Oktaviono; Suryo Ardi Hutomo; Kevin Luke (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Coronary artery disease (CAD) remains as the world number one cause of morbidity and mortality. Endothelial progenitor cells (EPCs) are known to be involved in vascular biology. Current review briefly summarizes the basics of EPCs and its clinical use in CAD.CONTENT: EPCs were firstly isolated in 1997 and involved in neovascularization. Further evidence defined EPCs into two distinguishable groups, namely: myeloid angiogenic cells (MACs) and endothelial colony forming cells (ECFCs). Common cardiovascular drugs, statin, angiotensin-converting enzyme (ACE) inhibitor, and their combinations, showed beneficial effects on EPCs. Likewise, the incorporation of EPCs upon CAD intervention management had been recently studied. Intramyocardial EPCs implementation and anti-CD34 antibody-coated stents could provide a promising option for refractory symptoms in CAD.SUMMARY: Association between EPCs and CAD is very dynamic and complex. EPCs could serve as both therapeutic target and agent in CAD patients. Subsequently, a universal definition of EPCs is needed for greater research in the future.KEYWORDS: atherosclerosis, coronary artery disease, endothelial progenitor cells, neovascularization